The Prevalence of Bacteriospermia in Infertile Men and Association with Semen Quality in Southwestern Iran - Motamedifar, Mohammad; Malekzadegan, Yalda; Namdari, Parisa; Dehghani, Behzad; Jahromi, Bahia N.; Sarvari, Jamal (Infectious Disorders - Drug Targets, 2020)
Introduction: Infertility considered as a social and public health issue and estimated that most of these infertile couples are residents of developing countries. Infectious diseases including the history of Sexually Transmitted Infections (STIs) may impact on male reproductive function. Therefore, the present study aimed to investigate the prevalence of bacterial contaminants of semen and probable association with sperm quality of infertile men in Iranian population. Methods: The study population consisted of 200 infertile men and 150 fertile men attending an infertility Center in southwestern Iran during the study period in 2015. The assessment of sperm parameters was according to the World Health Organization (WHO) guidelines. The presumptive pathogens were identified using standard microbiology tests and confirmed by specific PCR primers. Results: The prevalence of bacteriospermia in the semen of the infertile group was significantly higher than that in the fertile group (48% vs. 26.7%, P <0.001). The microbiological analysis of samples showed that the most abundant species of bacteria in semen of infertile men were Chlamydia trachomatis (12.5%) followed by Neisseria gonorrhoeae (11%). On the other hand, in the control group, Lactobacillus spp. (17.3%) was the most isolated pathogen. Results showed that the presence of N. gonorrhoeae, C. trachomatis, Mycoplasma genitalium, Haemophilus, and Klebsiella was significantly associated with sperm abnormality. Conclusions: Based on our findings, it seems that bacteriospermia is associated with alterations in the properties of semen which may lead to a decrease in the fertilization potential of sperm. Therefore, immediate and appropriate treatment is necessary before investigating every other possible cause of infertility.
Keywords: mycoplasma genitalium